OP63 The effects of the 2007–9 financial crisis on mental health in the uk: a longitudinal analysis of non-suicide mental health trends. (2nd September 2017) - Amies, B; Munford, L; Sutton, M
Abstract : Background: Existing research using area-level data has identified big increases in suicides in the UK and elsewhere through the financial crisis of 2007–09. Areas with larger increases in unemployment tended to have greater increases in suicide rates. The evidence base in this area has two particular weaknesses that this study aims to address. Firstly, this study uses individual-level data rather than aggregated area data, and secondly it examines non-suicide mental health trends rather than suicide rates. Methods: A nationally-representative sample of 12 816 individuals from the British Household Panel Survey in England from 2000–2013. Data were not collected for 2009. Fixed effects models were used to examine the data for associations between 12-item General Health Questionnaire score (measuring mental health) and demographic features, employment status and equivalised household income on the unweighted sample. Dummy variables for 2008–2010 (the period from the start of recession up to the start of government budget cuts) and 2011–13 (from the start of budget cuts) separated out the influence of changing economic conditions. Lagged and advanced variables were used to explore associations between mental health and the loss of income or employment through time. Results: Poor mental health peaked in 2008, before the peak in unemployment in 2010. Women and poorer people had significantly worse mental health throughout (p<0.000, beta 1.24 (95% confidence interval 1.08–1.40), p<0.000, beta 0.129 (−0.192- −0.065) respectively). Unemployment was significantly associated with worse mental health (p<0.000, beta 1.84 (1.52–2.16)). The association between mental health and income was weaker, with the most persistent effects for the period 2008–2010 (p=0.000, beta −0.64 (−0.88- −0.40)). Worse mental health appeared to preced job or income loss (p=0.028, beta 0.46 (0.049–0.88); p=0.011, beta 0.23 (0.051–0.40), respectively) but mental health did not deteriorate following job-loss, while increasing income appeared to compromise mental health (p=0.006, beta −0.24 (−0.42- −0.069)). Weighted sensitivity analysis confirmed a persistent association between unemployment and mental health but significance was lost between income and mental health. Conclusion: Non-suicide mental health deteriorated during the 2007–2009 financial crisis. It appears that worse mental health preceded job loss or income loss. A possible explanation could be that poor mental health conferred weakness in the job market. There are a number of inferences to the research area, for example that a strong social safetynet may protect mental health (by maintaining income) and that in-work mental health support may benefit poorer workers.